High-Sensitivity Dynamic Detection of Dissolved Acetylene in Transformer Oil Based on High-Power Quartz-Enhanced Photoacoustic Spectroscopy Sensing System - Yuxiang Wu; Tiehua Ma; Chenhua Liu; Yashan Fan; Shuai Shi; Songjie Guo; Yu Wang; Xiangjun Xu; Guqing Guo; Xuanbing Qiu; Zhijin Shang; Chuanliang Li (Photonics)
To enable the highly sensitive detection of acetylene (C2H2) dissolved in transformer oil, a high-power quartz-enhanced photoacoustic spectroscopy (QEPAS) sensing system is proposed. A standard 32.7 kHz quartz tuning fork (QTF) was employed as an acoustic transducer, coupled with an optimized acoustic resonator to enhance the acoustic signal. The laser power was boosted to 150 mW using a C-band erbium-doped fiber amplifier (EDFA), achieving a detection limit of 469 ppb for C2H2 with an integration time of 1 s. The headspace degassing method was utilized to extract dissolved gases from the transformer oil, and the equilibrium process for the release of dissolved C2H2 was successfully monitored using the developed high-power QEPAS system. This approach provides reliable technical support for the real-time monitoring of the operational safety of power transformers.